Effective Factors in Successful Establishment of Knowledge Management in Information and Communication Technology Companies - Mohammad Taghi Taghavifard, MehrdadKhodaverdian, Iman RaeesiVanani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nowadays, knowledge of employees is a very precious resource, which should be documented, developed, and shared among the members of a company. In order to work in the competitive world, companies must utilize their tacit and explicit knowledge in all their activities, and nothing as much as knowledge management (KM) processes can help companies to gain the competitive advantage. The present research aims to identify and measurethe effective factors in the successful establishment of KM in information and communication technology (ICT) companies. Grounded on a descriptive– survey research methodology, this research is a case study based on the data collected from182 companies belonging to Iranian ICT Guild Organization. The effective factors in the successful establishment of KM (the dependent variable) in ICT companies are human resources, processes, and information technology (the independent variables). According to the results, among the variables, the ‘processes’ variable has the most impact on the efficacy of establishment of KM (54.9%). It means that the ‘processes’ variable causes 54.9% deviations in the efficacy of KM establishment. Twenty-eight point one percent (28.1%) and 17.9% of the efficacy deviations are related to human resources and information technology, respectively. On the basis of a preliminary study, four processes are identified in KM, namely knowledge recognition, knowledge acquisition, knowledge codification, and knowledge sharing, which have significant effects on the establishment of KM. The findings indicate that the processes and in particular knowledge sharing have more significant contributions for ICT companies seeking the successful establishment of KM